A school-based rope skipping intervention for adolescents in Hong Kong: protocol of a matched-pair cluster randomized controlled trial - Ha, Amy S (BioMed Central, 2014)
BACKGROUND: Schools present venues for physical activity promotion among youth, with physical education (PE) considered the primary vehicle responsible for increasing activity levels. Yet students are not very physically active during typical school PE classes. With the aim to engage Hong Kong students in more moderate-to-vigorous physical activity (MVPA) during PE, a fitness infusion intervention using rope skipping was designed, and its effectiveness will be examined. Rope skipping was chosen because a) it provides moderate-to-high intensity physical activity; b) is inexpensive; c) students find it enjoyable; and d) is feasible in typical environments in Hong Kong, where PE classes are large in size (up to 40 students) and space available for physical activity is usually limited. METHODS/DESIGN: A matched-pair cluster randomized controlled trial was designed. Secondary school students from 24 classes (from 12 schools) will be recruited to participate in the trial. Students’ baseline MVPA will be measured during school PE. Classes will be matched according to baseline variables and one class from each pair will be randomized into the experimental group. Teachers in the experimental group will be invited to attend a teacher workshop, and will insert a 15-minute rope skipping activity in four consecutive PE lessons. Motivational factors based on self-determination theory will also be measured as secondary outcomes. The effectiveness of the intervention will be evaluated by comparing changes in the proportion of lesson time spent in MVPA from baseline to follow-up across the experimental and control groups. DISCUSSION: Physical activity levels in PE are often very low and there is a need to identify feasible low-cost interventions that can be easily disseminated. If the results of the study suggest the intervention to be effective, it could be implemented to schools throughout Hong Kong and other cities where space is limited. TRAIL REGISTRATION: ANZCTR: ACTRN12613000968774. Registered on 30 August 2013.